Penyuluhan Tatalaksana Awal Trauma Gigi pada Anak-anak Guru dan Wali Murid RA Al-Muttaqin - Jeddy; Dwimega, Arianne; Tegar Badruzzaman, Idham; Erfan, Erni; Ihsan Rizal, Muhammad; Anggraeni, Rezky (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Anterior tooth trauma often occurs in children because children are more active than adults and their coordination and assessment of conditions are not good enough, so they often fall while learning to walk, run, play and exercise. Trauma that occurs to a child's teeth can interfere speech, chewing, aesthetics and the eruption of permanent teeth, thereby disrupting the growth and development of the teeth and jaw. Therefore, it is important to pay attention to the approach regarding the first treatment of trauma to primary teeth for parents and children. The choice of Community Service target at RA Al-Muttaqin was due to a request from the school principal as community leader. Education and training activities were carried out on July 27 2023 for a total of 20 teachers and parents. The aim of this activity is to increase knowledge and motivate changes in attitudes and behavior in maintaining oral health and regarding first care for primary tooth trauma. The initial assessment of knowledge and attitudes regarding primary care for trauma to primary teeth and the mouth of teachers was carried out through a pre-test. Counseling on how to maintain healthy teeth and mouth, including dental and oral health problems, prevention methods, as well as first care for primary tooth trauma by the presenter as well as educational videos. As an evaluation, a post test was carried out. The evaluation of the post test results showed an increase in scores. Recommendations for continuing this training activity in other elementary schools, especially for teachers in the school environment.